Radiolucency in stemless shoulder arthroplasty is associated with an imaging phenomenon. Issue 9 (21st April 2017) - Hudek, Robert; Werner, Birgit; Abdelkawi, Ayman F.; Schmitt, Rainer; Gohlke, Frank
ABSTRACT: Stemless humeral implants show comparable midterm clinical results compared to stemmed components. Recently, radiolucencies around the metaphyseal seating of humeral stemless implants were reported on postoperative radiographs. It is controversial whether they are attributable to bone resorption. We hypothesized these radiolucencies result from imaging artifacts. Seven cadaveric specimens (three male and four female) were first radiographed and then scanned with CT. A stemless humeral component of current design was implanted in each specimen. After implantation, all specimens were radiographed with different exposure settings. The implant was removed, and the specimens were scanned with CT again. Pre‐ and post‐implantation radiographs and CT scans were compared. The mean Hounsfield units (HU) at the humeral resection plane from the pre‐implantation CT were correlated with the diameter of the radiolucent halo on the post‐implantation radiographs. A symmetric radiolucent halo of variable diameters occurred on all radiographs after implantation when an automatic exposure control was used. The halo disappeared in all specimens when the tube voltage was reduced. Lower CT‐values (HU) before the implantation resulted in greater halos on the radiograph after implantation. Symmetric radiolucent halos can result from imaging artifacts, which is most likely due to radiation scatter. The halos can be minimized by reducing the tube voltage. The halo effect appears to be pronounced in bones with decreased density. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2040–2050, 2017. Abstract : Radiolucencies around the metaphyseal seating in stemless humeral implants can be attributable to an imaging phenomenon. Cadaveric specimens were radiographed and CT scanned with and without a stemless humeral implant using different exposures. A radiolucent halo was constantly observed around the implant on radiographs. It disappeared when the tube voltage was reduced. Symmetric radiolucent halos can result from imaging artifacts, which is most likely due to radiation scatter. The halo effect appears to be pronounced in bones with decreased density.